2014
DOI: 10.1016/j.ijmedinf.2014.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and evaluation of an integrated computerized asthma management system in a pediatric emergency department: A randomized clinical trial

Abstract: Objective The use of evidence-based guidelines can improve the care for asthma patients. We implemented a computerized asthma management system in a pediatric emergency department (ED) to integrate national guidelines. Our objective was to determine whether patient eligibility identification by a probabilistic disease detection system (Bayesian network) combined with an asthma management system embedded in the workflow decreases time to disposition decision. Methods We performed a prospective, randomized con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 13 publications
1
56
0
Order By: Relevance
“…We previously analyzed our regional deployment of the iGuideline ECDS tool using Apsalar and found that, from its release in June 2013, it was downloaded by 937 users in the first year, resulting in 3013 user sessions and a median session length of 31.8 seconds 32 . Multiple previous reports have demonstrated the value of integrating ECDS into EHR systems to disseminate evidence-based practice recommendations 33–37 . However, these reports are based primarily on individual health systems or integrated networks that utilize the same basic EHR infrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…We previously analyzed our regional deployment of the iGuideline ECDS tool using Apsalar and found that, from its release in June 2013, it was downloaded by 937 users in the first year, resulting in 3013 user sessions and a median session length of 31.8 seconds 32 . Multiple previous reports have demonstrated the value of integrating ECDS into EHR systems to disseminate evidence-based practice recommendations 33–37 . However, these reports are based primarily on individual health systems or integrated networks that utilize the same basic EHR infrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…A Pediatric Asthma Severity (PAS) score was used and recorded by the PED staff (physicians, nurses and respiratory therapist (RT)) from 2005 to 2008. From 2009 to 2013, an individualised component input-derived PAS score was used by the triage nurse, RT, nurses and physicians for initial assessment, and to drive asthma therapeutic interventions10 18 19 (table 1). …”
Section: Methodsmentioning
confidence: 99%
“…In recent paediatric asthma trials, ventilation heterogeneity and individualistic β-2 receptor response to medications have been proposed as the aetiology of patient's variable response to bronchodilator therapy 7–9. Current aerosol systems can be ineffective in certain asthmatics with large airway obstruction and poor lung ventilation while CPAP or BiPAP has shown to be beneficial in these asthmatics 10–14. In acute asthmatics, BiPAP has a direct bronchodilator effect, achieves greater peripheral bronchodilator dispersal while unloading fatigued inspiratory muscles, offsetting auto positive end-expiratory pressure (auto-PEEP), recruiting collapsed alveoli all causing a reduction in their work of breathing and achieving their total lung capacity quicker 11–15…”
Section: Introductionmentioning
confidence: 99%
“…Asthma maladies analyze is absolutely subject to the sound that is made by the patient amid cough.A non asthmatic patient when hacks delivers a sound of recurrence (206 (14) Hz) where as an asthmatic patient on hack creates a sound with recurrence (239(19)Hz).There are different sound recording gadgets now a days that records the sound and demonstrates the recurrence of the sound from which it can be unmistakably analyze whether the sound is of a typical individual or of an asthmatic patient.On the premise of bronchial excessive touchiness the asthma has the accompanying sorts: hypersensitive asthma (atopic, extraneous, brought on by immunologic jolt of an antigen), natural (non-unfavourably susceptible, impelled by contamination, physically or artificially), practice affected, medication instigated asthma, occupative asthma and asthmatic bronchitis [3]. There are distinctive sort of sounds as indicated by diverse hypotheses.…”
Section: Types Of Asthmamentioning
confidence: 99%